CDL-CQI Template / Shahilah Nordin, Norsabrina Sihab and Lyly Nyl Ismail - Nordin, Shahilah; Sihab, Norsabrina; Ismail, Lyly Nyl (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Closing The Loop – Continual Quality Improvement (CDL-CQI) Template is a template developed for reporting the continual quality improvement processes at course level. It is being implemented for the Diploma in Electronic Engineering and Diploma in Electrical Engineering in UiTM. This template includes the process of monitoring, review, and CQI purposes for a course. For a programme to be accredited, it is important for the programme to have CQI processes, including documentation. Incomprehensible CQI documents and repetitive tasks for reporting are the main concerns. Due to these, the CDL-CQI template is created to assist the persons in charge in preparing a comprehensive Plan-Do-Check-Act (PDCA) cycle in CDLCQI report within a minimal time. CDL-CQI Template aims to facilitate the Resource Person (RP) to do the reporting of CDL-CQI at the course level; data entry, data analysis, data visualization and graphical display are becoming easier. Therefore, the documentations for accreditation purposes will be standardized, comprehensive, tangible and manageable. This template operates using Microsoft Excel. It is available offline, and provides flexibility – anytime, anywhere, on any devices, and is easy to use. It also requires basic skills and the most important is it implies no additional cost to the educational institution. It is expected to provide an assistance to the RP in data entry, data analysis, and observed the performance for the course performance reporting, which is significantly related to any educational programme. This CDL-CQI template has a high potential for commercialization in reporting course performance, monitoring, and review.